Loyalitas Karyawan Pada Perusahaan Spare Part Kendaraan - Ekananda, Enrico Julian; Rizqi, Maulidyah Amalina (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
Purpose–This study aims to determinedescription of employee loyalty at Vehicle Spare Part Companywith using 2 perspectives, namely employee loyalty to work and loyaltyemployees to Leaders. This research was conducted ina spring manufacturing industry, namely Vehicle Spare Part Company Design/methodology–This research is descriptive qualitative research with a case study approach. Data collection techniques include interviews and observation. The object of the research is employee loyalty, where the subjects are the 5 most senior employees in the maintenance department. Findings - Based on the research results, it can be concluded that Vehicle Spare Part Company employees have good loyalty, this can be seen from employee loyalty to work and employee loyalty to leaders.